Lowering Pulmonary Wedge Pressure after Heart Transplant: Pulmonary Compliance and Resistance Effect - Moreira,Nádia (2015)
AbstractBackground:Right ventricular (RV) afterload is an important risk factor for post-heart transplantation (HTx) mortality, and it results from the interaction between pulmonary vascular resistance (PVR) and pulmonary compliance (CPA). Their product, the RC time, is believed to be constant. An exception is observed in pulmonary hypertension because of elevated left ventricular (LV) filling pressures.Objective:Using HTx as a model for chronic lowering of LV filling pressures, our aim was to assess the variations in RV afterload components after transplantation.Methods:We retrospectively studied 159 patients with right heart catheterization before and after HTx. The effect of Htx on hemodynamic variables was assessed.Results:Most of the patients were male (76%), and the mean age was 53 ± 12 years. HTx had a significant effect on the hemodynamics, with normalization of the LV and RV filling pressures and a significant increase in cardiac output and heart rate (HR). The PVR decreased by 56% and CPA increased by 86%. The RC time did not change significantly, instead of increasing secondary to pulmonary wedge pressure (PWP) normalization after HTx as expected. The expected increase in RC time with PWP lowering was offset by the increase in HR (because of autonomic denervation of the heart). This effect was independent from the decrease of PWP.Conclusion:The RC time remained unchanged after HTx, notwithstanding the fact that pulmonary capillary wedge pressure significantly decreased. An increased HR may have an important effect on RC time and RV afterload. Studying these interactions may be of value to the assessment of HTx candidates and explaining early RV failure after HTx.